KASHMIR, BEFORE AND AFTER ARTICLE 370 - Jha, Pratiksha; Verma, Mukul Bihari (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Indian Supreme Court in 2023 had reiterated the government’s decision to abrogate article 370. This research paper will attempt to understand the challenges and collective issue related to article 370. This study will also attempt to capture the situation of Kashmir after abrogation of article 370. This paper will examine the effects of the abrogation of article 370 abrogation on the Jammu and Kashmir and the country as a whole. It also explores the character and legal nature of article 370. This paper will attempt to explore and analyse the political, social and economic implication of article 370, and also go on to examine the troubled history of article 370.